An investigation into the feasibility of culturing rat embryos in sheep serum for the detection of teratogenic substances in ewes - Burgman, Josepha Maria (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1990.